THE EFFECT OF USING PARTNER READING STRATEGY TOWARD READING FLUENCY AT THE 7TH GRADE STUDENTS’ OF SMP N 2 BATANG ANGKOLA - Harahap, Desiska Vianty (BRIGHT VISION Journal of Language and Education, 2021)
This research focused on discussing about the effect of using partner reading strategy as a new strategy toward students’ reading fluency in SMP N 2 Batang Angkola. In this case, the research method was quantitative research by using experimental method. the population of the research is the seven grade students’ in SMP N 2 Batang Angkola, the population of this research is the second year of the 7th grade students’ in SMP N 2 Batang Angkola, the sample was taken by using cluster technique. To take the control class and the experimental class. The instrument of this research is using reading narrative text, researcher give a pre-oral test and post- oral test to measuaring the student fluency in reading text. After analyzed the data used statistic calculation the researcher found that coeficient of t0bservation = 8.45 and the df (degree of fredom) is 36 and 36 in ttable at the level of significant of 5% is 2.03 and level significant of 1% is 2.72, so it can be write that 2.03<8.45>2.72 . So the result of this research showed that there is a significance effect of partner reading strategy toward student’s reading fluency. The seven grade students’ in SMP N 2 Batang Angkola Reading ability is increassing after using partner reading strategy. Keywords : Partner Reading Strategy, Reading Fluency